EFFECTS OF WA CYTOPLASM ON VARIOUS QUALITY CHARACTERISTICS OF RICE HYBRIDS - S. A. Waza; H. K. Jaiswal (Journal of Animal and Plant Sciences, 2014)
The differences between twenty pairs of AF1 (CMS line x restorer) and BF1 (maintainer line x restorer) cross combinations were evaluated to appraise the WA cytoplasmic influence on various quality traits of rice hybrids. The cytoplasmic influence for different traits was found to be highly cross-specific, depending on the nuclear background of CMS line and fertility restorer. Most of the traits were not significantly affected by the sterile cytoplasm in majority of the cross combinations. Only in some crosses, the cytoplasm has significant influence for majority of the traits studied. Most significant effect of the sterility inducing cytoplasm was reduction in length of cooked kernel, followed by decrease in amylose content. Male sterility inducing cytoplasm had no effect on aroma.
Keywords: CMS line; maintainer; restorer; WA cytoplasm; quality traits; rice hybrids